STEM to story : enthralling and effective lesson plans for grades 5-8 - Traig, Jennifer; 826 National (Organization) (San Francisco, CA : Jossey-Bass, a Wiley brand, 2015)
'Bring STEM to life for students with zombies, rockets, celebrities, and moreSTEM to Story: Enthralling and Effective Lesson Plans for Grades 5-8 inspires learning through fun, engaging, and meaningful lesson plans that fuse hands-on discovery in science, technology, engineering, and math (STEM) with creative writing. The workshop activities within the book are the innovative result of a partnership between 826 National's proven creative writing model and Time Warner Cable's Connect a Million Minds, an initiative dedicated to connecting young people to the wonders of STEM through hands-on learning. Authentically aligned with both the Common Core State Standards and the Next Generation Science Standards, this book provides teachers, after-school and out-of-school providers, and parents with field-tested lessons, workshops, and projects designed by professionals in each field. Including reflective observations by arts and science celebrities like Jon Scieszka, Mayim Bialik, and Steve Hockensmith, lessons feature bonus activities, fun facts, and teaching points for instructors at every level. These quirky, exploratory lessons will effectively awaken student imaginations and passions for both STEM and creative writing, encourage identity with scientific endeavors, and make both science and writing fun.Grades five through eight is the critical period for engaging students in STEM, and this book is designed specifically to appeal to - and engage - this age group. The guided curricula fosters hands-on discovery, deep learning, and rich inquiry skills while feeling more like play than school, and has proven popular and effective with both students and teachers. Awaken student imagination and get them excited about STEM Fuse creative writing with STEM using hands-on activities Make scientific principles relevant to students' lives Inspire students to explore STEM topics further The demand for STEM workers is closely linked to global competitiveness, and a successful future in STEM depends upon an early introduction to the scientific mindset. The challenge for teachers is to break through students' preconceptions of STEM fields as'hard' or'boring,' to show them that STEM is everywhere, it's relevant, and it's loads of fun. For proven lesson plans with just a dash of weird, STEM to Story is a dynamic resource, adaptable and applicable in school, after school, and at home'--
Machine generated contents note: Preface vii How to Use This Book ix Science-O-Pedia: A Glossary xix Acknowledgments xxv The Authors xxvii The Contributors xxxi LESSON PLANS 1 THE SCIENCE OF SAVING DAYLIGHT 1 Students learn the fundamentals of the scientific method as they write zany hypotheses to explain daylight saving time 2 TECHNICALLY SPEAKING 10 A challenge to make a high-performing paper airplane introduces students to the basic principles of both technical writing and engineering. observations by Loretta'Aleta' Jackson 3 IT'S (PARTIALLY) ROCKET SCIENCE AND (MOSTLY) ICE CREAM 26 Students explore physical properties and engineering principles by trans-forming a liquid into a solid -- ice cream! -- and then designing a struc-ture to keep it cool. observations by Mayim Bialik. 4 PLANET OOBLECK 38 Students get (a little) messy and (a lot) creative as they use gooey Oobleck to explore our universe and the life forms that inhabit it. Observations by Colonel Chris Hadfield. 5 HOW TO WRITE SCIENCE FICTION 58 In this writing-intensive lesson, students learn to apply scientific prin{u3A70}les and their own imagination to create great stories. Observations by Mac Barnett. 6 MAKING WAVES 67 Students discover the connections between music and math by making their own instruments and exploring the properties of sound waves. 7 THERE MAY BE BONES 84 Shh. it's a mystery. Students use their deductive skills to identify what, exactly, is in a mysterious nugget, learning about biology as they do so. Observations by Jeff Corwin. 8 TINFOIL SHIPBUILDING 103 Engineers, ahoy! Students put their skills to the test designing seawor{u4A39} tinfoil boats, learning about density along the way. Incorporating their newfound knowledge, they then launch some thrilling tales. 9 WATER, WATER EVERYWHERE, NOR ANY DROP TO DRINK 117 Water is important to just about every STEM discipline. In this thor{uFD67}h lesson, students explore the properties of water across various fields by polluting water, then creating filters to purify it. 10 THE SCIENCE OF SUPERPOWERS 138 In this superlesson, students isolate DNA, design planes, build lairs, and engineer safe transport to help a hero save the day. Observations by Jon Scieszka. 11 INFINITE RECESS 189 Math meets poetry in a lesson that's as fun as it sounds. 12 REWRITING THE ZOMBIE APOCALYPSE 210 It's a final exam with everything on the line as students are called on to apply all their scientific knowledge to outsmart zombie invaders. Observations by Steve Hockensmith. APPENDIX Handy Lesson Links 245 Self-Assessment Checklists 254 Common Core Curriculum Standards for English Language Arts 258 Next Generation Science Standards 275 Student Survey 291 826 Centers and Staff 293 INDEX 297 .
Includes index.
Keywords: Science -- Study and teaching (Elementary).; Creative writing (Elementary education).